Analisis Persepsi Guru Tentang Pembelajaran Berbasis Daring Di Sekolah Dasar - Windi Saputri Marta; Luthfi Hamdani Maula; Andi Nurrochmah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This Study Aims To Analyze Teacher Perceptions In Online-Based Learning, Teacher Perceptions And Factors That Can Support The Online Learning Process During The Covid-19 Pandemic. This Research Uses Descriptive Qualitative Research Methods. The Subjects Used In This Study Were Class Teachers At SDN Babakan Sirna. The Sampling Technique Used Was Purposive Sampling, Where The Data Source Sampling Technique Was Carried Out With Certain Considerations. Data Collection Techniques In This Study Using Interviews And Documentation. The Data Analysis Technique Uses The Stages Of Data Reduction, Data Display, And Conclusion Drawing / Verification. The Result Of This Study Is The Teacher's Perception Of The Online Learning Process, Which Is Usually Carried Out Directly In Schools, Now Transferred To Their Respective Homes Into Online Learning. In The Online-Based Learning Process That Is Carried Out Is Still Ineffective Because Students Feel Bored And Bored Because During The Implementation Of Online Learning They Do Not Interact Directly With The Teacher And Their Friends. There Are Several Perceptions Of Teachers About Online Learning, In Addition To Teacher Perceptions, Factors That Can Support The Online Learning Process, Namely The Availability Of Mobile Phones, Quotas And Stable Internet Connections And The Role Of Parents.Supporting Factors; Online Learning; Teacher Perception.